Psychological distress, coping strategies, and quality of life among house officers in East Coast Malaysia hospitals - Abdul Rafa, Ainin Tasneem; Zakaria, Rozanizam; Mohd Yasin, Mohd Azhar; Alias, Siti Afifah; Saemar, Roslan; Hashim, Aini Hayati; Saad, Siti Syazana; Azim, Nur Syamimi (Wolters Kluwer - Medknow, 2025)
Background: Housemanship is a critical transition for medical graduates, often marked by psychological distress due to high workloads, long hours, workplace stress, and career uncertainty. This study explores the prevalence, determinants, and impact of psychological distress, coping strategies, and quality of life (QoL) among house officers in East Coast Malaysia.